Evaluating and Mitigating Musculoskeletal Risks among the Operators: A Case Study in a Small-Scale Automotive Repair Workshop - Rini Oktavera; Muh Ilal Sarifudin; Wahyu Eko Cahyono; Moh. Ainul Fais; IGA Sri Deviyanti (Jurnal Penelitian Pendidikan IPA, 2025)
Musculoskeletal Disorders (MSDs) are a prevalent issue among lathe operators in small automotive repair workshops, largely due to repetitive movements, prolonged static positions, and awkward postures. This study employed the Nordic Body Map (NBM) and Workplace Ergonomic Risk Assessment (WERA) to evaluate ergonomic risks and identify affected body areas among lathe operators at XYZ workshop. Results indicate significant discomfort in the lower back, neck, shoulders, and wrists, linked to static postures and repetitive motions required for lathe operations. WERA scores revealed moderate ergonomic risks, particularly involving shoulder posture and work duration. Visual summaries in the form of bar and radar charts illustrate key risk factors. To mitigate these risks, the study proposes low-cost ergonomic interventions such as workstation adjustments, anti-vibration gloves, regular breaks, posture training, and rotational work schedules. These interventions not only address immediate discomfort but also have long-term potential for reducing MSDs when integrated into worker training programs. Moreover, the study’s findings can be utilized as contextual learning materials within applied science education (IPA terapan) at vocational schools (SMK), fostering ergonomic literacy among students and educators.This study fills a significant gap in ergonomic research in informal micro-industry settings and offers actionable insights for both occupational health improvement and science-based curriculum development in vocational education.